Comperative Study of Laser Haemorrhoidoplasty and Miligan-Morgan Haemorrhoidectomy in 2nd and 3rd Degree Haemorrhoid - Bhuiyan, Md Nur Hossain; Nath, Pradip Kumar; Shaha, Emon Kalyen; Khan, Hussain Ahmed (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Arterial overflow in the superior hemorrhoidal arteries would lead to dilatation of the hemorrhoidal venous plexus, according to the ‘‘vascular’’ theory. Hemorrhoid laser procedure (LHP) is a new laser procedure for outpatient treatment of hemorrhoids in which hemorrhoidal arterial flow feeding the hemorrhoidal plexus is stopped by laser coagulation. Compare the hemorrhoid laser procedure with Miligan-Morgan open surgical procedure for outpatient treatment of symptomatic hemorrhoids. Material and methods: This study was conducted at Chittagong Medical College Hospital (CMCH) and Private Hospital in Chittagong. Patients with symptomatic grade II or grade III hemorrhoids with minimal mucosal prolapse were eligible for the study: 30 patients treated with the laser hemorrhoidoplasty, and 30 patients–with Miligan-Morganhemorrhoidectomy. Operative time and postoperative pain with visual analog scale, were evaluated. Results: A total number of 60 patients (33 men and 27 women, mean age 45 years) entered the trial. Significant differences between laser hemorrhoidoplasty and Miligan-Morgan surgical procedure were observed – i) Operative time ii) Early postoperative pain. There was a statistically significant difference between the two groups regarding peri-operative and the early postoperative period: 1 week, 2 weeks, 3 weeks and 1 month after respective procedure. Conclusions: Laser hemorrhoidoplasty procedure is more preferred in comparison with conventional open surgical hemorrhoidectomy. Postoperative pain is significantly lesser in laser procedure compared with surgical procedure JCMCTA 2020 ; 31 (1) : 86-89